Erdheim–Chester disease: A rare cause of recurrent fever of unknown origin mimicking lymphoma. (January 2014) - Mariampillai, Anusiyanthan; Sivapiragasam, Abirami; Kumar, Amit; Hindenburg, Alexander; Cunha, Burke A.; Zhou, Jianhong
Abstract We report the case of a patient with recurrent fever of unknown origin (FUO) with prominent back pain, hepatosplenomegaly, and abdominal/pelvic adenopathy suggesting lymphoma. A bone biopsy showed histiocytic infiltration. Studies for lymphoma were negative, but immunohistochemical stains were diagnostic of Erdheim–Chester disease (ECD). ECD should be included as a rare cause of recurrent FUO with bone involvement.